MODERN INNOVATIVE TECHNOLOGIES AND APPROACHES IN THE LEARNING PROCESS WITHIN THE MODERN EDUCATUIONAL ENVIRONMENT - NizamovaYelena Erkinbayevna (Journal of new century innovations, 2024)
Abstract: In the field of modern education and innovative technologies understanding of best practices, approaches to education, and modern lessons this article discusses the specific features of transition methods.